The Stagnation of Early Buddhist Studies in the Jabodetabek Area (A Case Study of the Dhammacitta Buddhist Community and the Early Buddhist Society of Indonesia) - Arya Whisnu Karniawan; Ida Bagus Gde Yudha Triguna; I Gusti Agung Paramita (Ridwan Institute, 2026)
Technological developments are increasingly rapid, including in Buddhism in Indonesia. Sectarian differences are also increasingly apparent. Efforts are needed to teach common or cross-sectarian Buddhist values. The study of Early Buddhism is seen as promising but remains very limited in the Jabodetabek. There are no Buddhist Higher Education Institutions that teach it, and there are only two forums that focus on this study, namely DhammaCitta and the Early Buddhist Society of Indonesia. There is a significant gap: Why is this study still so limited and not developing despite the existing need? This study aims to (1) Analyze the factors causing the stagnation of Early Buddhism Studies in Jabodetabek; (2) Analyze the process of this stagnation; (3) Analyze the impact of stagnation on the development of Buddhism studies in Jabodetabek. This research is a qualitative case study conducted in Jabodetabek. Data collection used observation, literature review, and unstructured in-depth interviews, using purposive sampling. Data analysis used verstehen, data interpretation, and heuristics. Data validity was ensured through Mahapadessa parallelization and data triangulation. The study of Early Buddhism in the Jabodetabek area has experienced stagnation caused by eighteen factors, consisting of major factors: (1) Low interest, (2) Trolling and negative discussion, (3) Busyness / time constraints, (4) Lack of adaptation to technological developments, (5) The Indonesian Buddhist ecosystem, (6) The natural character of Early Buddhism, (7) Enforcement of rules, (8) Antipathy and rejection. And minor factors: (1) Lack of desire for expansion, (2) The Covid-19 pandemic, (3) Information overload, (4) Running out of discussion topics, (5) non monks-based community, (6) Forcing Early Buddhism, (7) Lack of competent teachers, (8) No formal organization, (9) emotional burnout, and (10) poor promotion. The stagnation process occurred through social exchanges within the two communities, which tended to involve negative emotions accompanied by various obstacles. This resulted in stagnation in the quality of dissemination, which led to a decline/ cessation of the role of all members as guardians of tradition. The impacts of stagnation on Buddhist Studies in Jabodetabek are: (1) Loss of clarity between early and later traditions, (2) Worsening the obesity of information, (3) Loss of the deradicalization process, (4) The occurrence of a cultural negotiation process that destroys the fundamental principles of Buddhism, (5) Hindering integration into formal education.